Acral Folliculocentric Extragenital Lichen Sclerosus: A Case Report - Al-Husain KM; Madani A; Alhumidi A; Alsehli T; Nagshabandi KN (Dove Medical Press, 2024)
Khalid M Al-Husain,1 Abdulaziz Madani,2 Ahmed Alhumidi,3 Turky Alsehli,2 Khalid Nabil Nagshabandi2 1Department of Dermatology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Pathology, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid Nabil Nagshabandi, Email khalidnagshabandi@gmail.comIntroduction: Lichen sclerosus is a chronic inflammatory dermatological condition of unknown etiology, primarily impacting the genital epidermis in individuals of all genders, with a higher prevalence observed among postmenopausal women and prepubescent girls. Additionally, extragenital manifestations occur in approximately 20% of the patients diagnosed with genital lichen sclerosus. Notably, folliculocentric extragenital lichen sclerosus is rare and unusual, with only limited instances documented in existing literature.Case Description: We report a 33 years old lady presented with multiple asymptomatic lesions on the dorsal feet for 1 year and similar lesions on the left hand for 4 months. On examination: folliculocentric, shiny, atrophic papules coalescing into reticulated plaques over the dorsum of both feet and few shiny, flat-topped, pink papules over the dorsum of the left hand. A skin biopsy was performed and confirmed the diagnosis of extragenital lichen sclerosus.Conclusion: Acral folliculocentric extragenital lichen sclerosus is an unusual and rare clinical variant. Clinicopathologic correlation is necessary to establish the correct diagnosis.Contribution to the Literature: Herein, we present an unusual presentation of extragenital lichen sclerosus, and we highlight the importance of considering it in the differential diagnosis of guttate acral skin lesions. We also review and summarize relevant cases from the literature in hope to aid physicians, especially dermatologists, to consider and swiftly reach the diagnosis and offer appropriate management. We also hope to bring about new insights and broaden future research efforts regarding lichen sclerosus especially and atrophic skin disease in general.Keywords: lichen sclerosus et atrophicus, lichen sclerosus, morphea, anetoderma